Predictive value of Computed Tomography Coronary Angiography for the evaluation of acute chest pain: single center preliminary experience - Maffei, E.; Palombo, A.; Martini et al., C. (Acta Biomedica Atenei Parmensis, 2011)
Aim: To assess the predictive value of CT coronary angiography (CT-CA) in the stratification of patients with acute chest pain. Materials and methods: We enrolled 48 patients (31 males and 17 females, mean age 61.0±14yrs) with acute chest pain of suspected coronary origin, without diagnostic alterations of the ECG and/or increase of the myocardial biomarkers. Sixty-four slice CT-CA was performed within 48-72 hours. Depending on the clinical judgment, the patients were dismissed or underwent conventional coronary angiography (CAG). Patients underwent clinical follow-up at 6 months, recording the prevalence of major cardiovascular events. Results: One patient was excluded from the analysis because of poor image quality. CT-CA showed no coronary artery disease in 38.3% (18/47) of the patients, no significant coronary artery disease (<50% lumen reduction) in 31.9% (15/47) of the patients, significant coronary artery disease (≥50% lumen reduction) in 29.8% (14/47) of the patients. In 87.2% (41/47) of the patients no indication for CAG was present. In 6 (12,8%) patients with significant stenosis at CT-CA indication for CAG was present. In 50% (3/6) of these patients, CAG showed no significant coronary artery disease and in the remaining 50%(3/6) CAG was followed by percutaneous coronary angioplasty. At follow-up no major cardiovascular events were observed. Conclusions: CT-CA showed high sensitivity for the detection of significant coronary artery disease and a negative predictive value at 6-month follow-up.